2009
DOI: 10.1007/s12206-009-0207-9
|View full text |Cite
|
Sign up to set email alerts
|

The effect of nonequilibrium condensation on hysteresis phenomenon of under-expanded jets

Abstract: Under-expanded jets which are discharged from an orifice or a nozzle have long been subject of researches for aeronautical and mechanical applications. Provided that the jet pressure ratio and nozzle configuration are known, the major features of the steady jet are now well known. However, the jet pressure ratio is often varied even during the process in many practical applications. Many questions remain unanswered with regard to how the supersonic jet responds to the transient process of the pressure ratio an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…Eventually, some numerical studies seem to underline an hysteresis in this position in function of the pressure ratio [41,130,21,115].…”
Section: Positionmentioning
confidence: 99%
“…Eventually, some numerical studies seem to underline an hysteresis in this position in function of the pressure ratio [41,130,21,115].…”
Section: Positionmentioning
confidence: 99%
“…The critical pressure for Mach to regular reflection transition was found to depend on the flow history, and a hysteresis loop was calculated [17]. The damping effect of nonequilibrium condensation on hysteresis was examined by Kim et al [19]. Pressure ratios of 3.0 to 6.2 were examined in increments of 0.1 in simulations and experiments.…”
Section: Introductionmentioning
confidence: 99%
“…As in most of the engineering applications of supersonics jets, the working gas is usually steam or moist air and the moist air jets are qualitatively similar to dry air, but non-equilibrium condensation in moist air jet affects the shock configuration, reported by Baek et al [9] and Otobe et al [10]. Meanwhile, Kim et al [11] and Otobe et al [12] have investigated the effect of non-equilibrium condensation on the hysteresis phenomenon of under-expanded supersonic jets and reported that the moist air jet reduced the hysteretic phenomenon compared with the dry air jet, and the non-equilibrium condensation that occurs in the under-expanded moist air jet is responsible for these findings. However, only a few works have, to date, been devoted to the hysteresis phenomena for the reflection type of shock wave and for instance, the transitional pressure ratio between the regular reflection (RR) and…”
Section: Introductionmentioning
confidence: 99%